THE DEVELOPMENT OF TOONDOO ONLINE COMIC BASED ON RME TO SUPPORT STUDENT’S MATHEMATICAL LITERACY SKILLS - Rohati Rohati; Ade Kumalasari; Marlina Marlina; Naya Junia (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This research aims at 1) Developing a valid, practical, and effective Toondoo online comic media based on realistic math education (RME) on relations and functions material in junior high school, 2) Knowing whether RME- based Toondoo online comics can improve mathematical literacy skills. The research type is research and development with the ADDIE development model but the implementation stage is not carried out.  The population of this research was all eighth grade students of SMPN 7 Jambi.  Grade VIII H was taken as the sample of Toondoo online comic research. Response questionnaire and test are the data instruments for a validity, practicality and effectiveness of research. Post-test after learning Toondoo online comic is used as the instrument for mathematical literacy skills. Based on data analysis, the average validation of material, media and design experts falls into the  very valid category. The results of the practicality of Toondoo online comic media based on RME are practical, making it worth testing in the learning process. The results of the learning test state that students’ average value is 85.88 and mastery learning is 94.12%.  The results of post-test students’ mathematical literacy skills state that the average class is at level 3 and above with a percentage of 91.17% which is very good criteria. Based on student learning outcomes and post-test, online comic media based on RME is effective to be used in learning process in order to improve students’ mathematical literacy skills.